High Concentrator Photovoltaics Fundamentals, Engineering and Power Plants - Pérez-Higueras, Pedro.; Pérez-Higueras, Pedro.; Fernández, Eduardo F.; Fernández, Eduardo F. (Green Energy and Technology, 2015)
The aim of this book is to provide a comprehensive overview of the fundamentals and engineering of high concentrator photovoltaic (HCPV) technology and to elucidate how this complex and emerging technology is applied in power plants. It is the first of its kind to focus exclusively on HCPV technology, and offers a valuable reference volume to readers. This book is the result of an international collaboration among experts, and each chapter is written by a specialist in the field. The conversion of solar energy to electricity plays an important role in power generation, and HCPV is signalled by many researchers and professionals as one of the most promising sources of solar power. Therefore this book provides an important resource for companies, research institutes and universities to assist with the understanding of fundamentals, different applications and potential of such technology.